Endoreplication - Zielke, Norman; Edgar, Bruce; DePamphilis, Melvin L. (Cold Spring Harbor perspectives in biology, 2013)
Developmentally programmed polyploidy occurs by at least four different mechanisms, two of which (endoreduplication and endomitosis) involve switching from mitotic cell cycles to endocycles by the selective loss of mitotic cyclin-dependent kinase (CDK) activity and bypassing many of the processes of mitosis. Here we review the mechanisms of endoreplication, focusing on recent results from Drosophila and mice.
Gesehen am 28.07.2021